MAIN ASPECTS IN LANGUAGE TRAINING OF NON-ENGLISH SPEAKING AIRMEN - Pazyura, Nataliya (Proceedings of National Aviation University (archive), 2016)
In the globalized world and rapid development of technical progress aviation industry has been gaining more importance for humanity and requires a deeper understanding of the English language, its basic characteristics and mechanisms of functioning. Purpose: The aim of the article is to study the influence of the proficiency of English on flight safety, to consider the main communication problems of non-English speaking aviation personnel, highlight possible directions for training English-speaking personnel. In the article the author tries to show the disadvantage at which non-English speaking airline staff work in case of emergency. The article highlights the issue about high level aviation English proficiency necessary to avoid communication problem. Methods: For the research scientific general methods have been used which are main ways of studying scientific sources, and comparative method for synchronic comparison of events in the different regions. Results: The author concludes that at the same time it is necessary for aviation personnel to master plain language for understanding context of communication, to minimize uncertainty and improve understanding between the controller and pilot. Discussion: It stresses the idea that the language proficiency level that exceeds the minimum standards according to ICAO, contributes significantly to the reduction of communication problems and in such a way ensures safety.